Bertrand Westphal, Geocriticism, Real and Fictional Spaces - Mahmoud Kamali (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Geocriticism, Real and Fictional Spaces is a book by Bertrand Westphal, Professor of Comparative Literature at the University of Limoges in France. He is the theorist of geocriticism and has written several books to explain the importance of adopting a geocritical approach in literary studies. The book is an interdisciplinary study and was translated from French to English by Robert Tally who has written a preface to the book. The book is comprised of an introduction, five chapters, notes and an index. The chapters are entitled as follows: Spatiotemporality, Transgressivity, Referentiality, Elements of Geocriticism, and Reading Spaces. The first chapter is about temporal metaphors and spatializing time. In chapter two, the focus is on a characteristic element of contemprary space. Chapter three is devoted to theoretical speculations about links between the world and the text and between the referent and its representation. Chapter four describes the geocritical metodology. The final chapter examines the importance of the text in the construction of a place.